Pengaruh Kebijakan Dividen, Profitabilitas, dan Leverage terhadap Harga Saham pada Perusahaan Non-Cyclical yang Terdaftar di BEI - Nur Laila Eka Sari; Endang Masitoh Wahyuningsih; Suhendro (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to test and analyze the influence of dividend policy, profitability and leverage on stock prices. The research uses 2018-2022 non-cyclical companies listed on the IDX as the population. The sampling technique in this research used a purposive sampling technique so that 45 samples were selected that met the criteria. The data analysis technique used is multiple linear regression analysis test. The research results show that the Dividend Payout Ratio (DPR) has no effect on stock prices, while Return on Equity (ROE) and Debt to Equity Ratio (DER) have an effect on stock prices.